2008 10th IEEE International Workshop on Advanced Motion Control 2008
DOI: 10.1109/amc.2008.4516157
|View full text |Cite
|
Sign up to set email alerts
|

Time-energy optimal path tracking for robots: a numerically efficient optimization approach

Abstract: This paper focuses on time-optimal and time-energy optimal path tracking, which are subproblems in optimal motion planning of robot systems. Through a nonlinear change of variables, the time-energy optimal path tracking problem is transformed here into a convex optimal control problem with a single state variable. A direct transcription method is presented that reduces finding the globally optimal trajectory to solving a second-order cone program using robust numerical algorithms that are freely available. App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 24 publications
0
26
0
7
Order By: Relevance
“…With reference to Verscheure and Demeulenaere [15], we define states a and b that satisfy (12) Then, it is obvious that…”
Section: Non-smooth Trajectory Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…With reference to Verscheure and Demeulenaere [15], we define states a and b that satisfy (12) Then, it is obvious that…”
Section: Non-smooth Trajectory Generationmentioning
confidence: 99%
“…Gasparetto and Zanotto [14] used the fifth-order B-splines to define the path and solved the trajectory planning problem using the sequential quadratic programming (SQP) method. Verscheure and Demeulenaere [15] converted the time-optimal path tracking problem into a second-order convex programming problem which is then solved using the direct transcription approach.…”
Section: Introductionmentioning
confidence: 99%
“…Many short-time control methods based on these studies have been suggested since then (for e.g. [6]). In many of these studies, a sequence of q from a given initial position/posture q 0 to a given goal position/posture q g is pre-specified.…”
Section: Traditional Approachesmentioning
confidence: 99%
“…Shin and McKay presented a dynamic programming approach to trajectory planning for this step in [8]. Verscheure et al transformed the trajectory planning by direct transcription and used second order cone programming [9]. Moreover, it is also possible to integrate both path planning and trajectory planning in one stage by the means of mathematical programming, e.g.…”
Section: Introductionmentioning
confidence: 99%